2014
DOI: 10.12765/cpos-2014-10
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Norms and Actions<br>The Case of Men’s Participation in Housework<br>

Abstract: Gender and family researchers are often puzzled by the differences between gender norms and actual behaviour. For example, many previous studies have shown that since the 1970s, attitudes have changed toward more modern gender role beliefs. However, this is generally not reflected in behaviour, this being especially true for men’s involvement in housework and care work. In this paper, we analyse to what extent gender norms correspond with men’s participation in housework. We examine in particular cooking, vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Although men are, on average, less likely to endorse egalitarian gender ideologies than their female counterparts, when they do, they are more likely to take an active role in housework (Grunow and Baur 2014; Kroska 2004) and child care (Evertsson 2014). That is, men who hold the prescriptive belief that men ought to be primarily breadwinners and women ought to be primarily homemakers are, not surprisingly, less likely to share household and family responsibilities with their spouse.…”
Section: The Role Of Men’s Gender Ideologies and Masculinity Normsmentioning
confidence: 99%
“…Although men are, on average, less likely to endorse egalitarian gender ideologies than their female counterparts, when they do, they are more likely to take an active role in housework (Grunow and Baur 2014; Kroska 2004) and child care (Evertsson 2014). That is, men who hold the prescriptive belief that men ought to be primarily breadwinners and women ought to be primarily homemakers are, not surprisingly, less likely to share household and family responsibilities with their spouse.…”
Section: The Role Of Men’s Gender Ideologies and Masculinity Normsmentioning
confidence: 99%
“…However, recent research from Germany indicates a growing acceptance of childfree existences, particularly among urban and highly educated individuals (Bernardi, Mynarska, and Rossier 2015; Bujard 2015). Second, the relation between parenthood and life satisfaction is shaped by normative expectations regarding men’s and women’s involvement in various domains such as housework, child care, and employment (Moore and Abetz 2019; Stavrova and Fetchenhauer 2015; for Germany, see Grunow and Baur 2014; Lück 2006). The literature, both German and international, indicates that these expectations have developed differently for men and women and that new expectations have emerged for both (Lück 2006; Moore and Abetz 2019).…”
Section: Life Satisfaction After the Transition To Parenthoodmentioning
confidence: 99%
“…The recent shift toward fathers’ stronger involvement in their children’s upbringing was triggered by a change in gender roles for women. The “new father” is expected to take on a nurturing role and to be involved in parenting tasks (Dermott 2008; Gerson 2002; for Germany, see Grunow and Baur 2014; Kruse 2017). Even though there are country and class differences in the speed and scope of the diffusion of these emerging fatherhood norms, the direction is almost universal across Western countries (Kruse 2017; Plantin, Månsson, and Kearney 2003).…”
Section: Life Satisfaction After the Transition To Parenthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research in the field of gender role attitudes has shown all kinds of individual socio-demographic variations in gender role attitudes, even for very different dimensions of housework (e.g., Askari et al 2010;Braun & Scott 2009;Cunningham 2001;Dempsey 2001;Grunow & Baur 2014;Kroska 2003;Ogletree, Worthen, Turner & Vickers 2006;Pampel 2011;Poortman & van der Lippe 2009;Robinson & Milkie 1998;Spitze & Loscocco 2000;van Berkel & de Graaf 1999). However, there is a knowledge gap if these attitudes differ in potential situations of couples that are independent of the respondents' own sociodemographic situation (Auspurg, Iacovou & Nicoletti 2017;Carriero & Todesco 2016Doan & Quadlin 2019).…”
Section: Introductionmentioning
confidence: 99%